Assessing the exchange rate exposure of US multinationals - Patrick M. Crowley; Amir Habibdoust (Bank of Finland, 2013)
This paper aims to examine the relationship between exchange rate movements and the stock return of firms at different time horizons by employing wavelet analysis. In particular, we use the maximum overlap discrete wavelet transform (MODWT) to decompose the exchange rate movement and the US firm's stock return over the period January 2006 to July 2012. The results reveal that at longer horizons not only does the number of firms which are exposed to exchange rate volatility increase but also the degree of exchange rate exposure increases. What is more, the sensitivity to exchange rate volatility is stronger at longer horizons for importing firms than for exporting firms, which shows an asymmetry in the usage of hedging strategies between importers and exporters.
URN:NBN:fi:bof-20140807130
Keywords: C32; F31; F23; 330; Discrete Wavelet analysis; Exchange Rate Volatility; Hedging strategy